The Effect of Machining Parameters of Water Surface Tool Wear 6061be on 500 Watt Mini Cnc Machining Using Straight Endmill Carbide Tool With the Taguchi Method - Napitupulu, Richard; Perangin Angin, Siwan; Voice Sihombing, Hendrik (Talenta Publisher, 2024)
In today’s world in the manufacturing sector, turning plays a vital role among all other cutting methods. The cutting technique of the material is one of the important things that determine the quality of the product, while the cutting parameters and conditions also play an important role in the machining process. Selecting effective cutting condition parameters is very important to ensure product quality, extend tool life, reduce production costs, reduce carbon emissions, and improve production efficiency. In the turning operation of CNC Router 3 Axis Mach 3, machining parameters and tool geometry play an important role, Optimization of machining parameters increases the economic value of machining and also increases the value of the product. In this study, Taguchi method with fuzzy logic is used as an efficient approach to determine the optimal machining parameters for CNC Router 3 Axis Mach 3 lathe parts for optimizing Tool Wear on Workpiece. Experimental design using L16 43 OA orthogonal array for 2 controllable factors, namely, cutting speed and depth of cut, each at three levels to find the optimal combination of factors and levels in high-speed CNC Router 3 Axis Mach 3 turning of Aluminum Alloys 6061. From Taguchi analysis, it is known that the order of parameters that affect the tool life is the first variable Cutting Speed , second Feed, third Depth of Cut